Sinonasal malignancies: a retrospective review of a tertiary center experience - Gani, Kaamil (2023)
Objectives: To characterize demographics, presentation, histologic types, treatment and survival of patients with sinonasal malignancies diagnosed at a tertiary hospital center in Portugal. Study design: Retrospective study. Material and methods: Review of clinical records from January 2012 to December 2021. Results: Nineteen patients were included, with male predominance (57.9%) and a mean age at diagnosis of 66.7 ± 9.8 years. The most common presenting symptoms were nasal obstruction and epistaxis (47.4%). Squamous cell carcinoma was the most common histologic subtype (21.1%). Primary surgical therapy was preferred comparative to nonsurgical therapy (84.2% VS 15.8%). Nine patients were submitted to external approach, while 7 patients underwent endonasal endoscopic treatment. The mean follow-up time was 26.9 ± 20.6 months. Five-year overall survival was 53.5% and disease-free survival was 62.8%. Conclusion: In this study prognosis was stage and treatment-dependent, and  endoscopic approach was safe and effective in carefully selected patients.